(untitled) (Journal of Natural History Museum, 2015)
A total of 495 stool samples from the school children aged 9-12 years from Bhaktapur were examined for helminth parasites by direct smear method. Out of 495 children, 137 (27.68%) were found positive for one or more intestinal helminthic parasites. Ascaris lumbricoides (22.63%) showed highest prevalence rate followed by Trichuris trichiura (6.06%), Strongyloides stercoralis (1.82%), Hookworm (1.62%), Taenia sp. (1.01%), Hymenolepis nana (0.81%) and Enterobius vermicularis (0.40%). The helminthic infection was found to be almost equal in male and female children and statistically no signifi cant difference was found (χ2 = 8.31×10-6, p>0.05). Higher percentages of students were infected with single parasites than double and multiple infections. All 137 positive cases were treated with single oral dose of 400 mg albendazole. Post-treatment stool samples were collected four weeks after treatment to determine the cure rate. Stool samples were again collected 24 weeks post-treatment to study the rate of reinfection. The Cure Rates (CR) for A. lumbricoides was 61.82%, S. stercoralis was 66.67%, Taenia sp., Hookworm and E. vermicularis were 100%, T. trichiura was 44.83% and H. nana was 0.00%. The post treatment examination after 24 weeks showed that re-infection was present in A. lumbricoides (20.29%) and T. trichiura (7.69%) only. New infection was recorded for A. lumbricoides (21.74%), T. trichiura (4.72%), S. stercoralis (1.60%) and E. vermicularis (0.76%). The study showed albendazole was comparatively less effective against S. stercoralis, A. lumbricoides and T. trichiura which may be due to development of drug resistance at certain level which needs to be explored. J. Nat. Hist. Mus. Vol. 28, 2014: 93-101